Książka w środowisku lokalnym i regionalnym - Wojciechowski, Jacek (Biblioteka Uniwersytecka w Poznaniu, 2007)
The changes that are currently taking place in public communication, especially those influenced by IT, have triggered opinions that traditional forms of communication, especially paper forms, are on the verge of extinction. In fact, however, complementary coexistence of both forms of communication, after a careful segmentation process of functioning areas, is more likely to happen. E-communication is commonly identified with information, whereas, like the whole of communication, it is rather fragmented into informative and non-informative. What is really new in it, is its interactive character, substantial freedom in reception, deepened immersion, though temporality as well. It is just another form of communication though it cannot entirely substitute all traditional forms. Public communication functions within a wide spectrum of social life - both within its inner spaces and between them and this situation does not necessarily involves conflict. The local space and, partly, the regional one always shapes the reception, whereas the transmission, though to a various degree depending on a given form of communication, generates itself mainly in the global and/or all-national dimensions. There are some variances in transregional areas. From this perspective, the book is a tool, mainly from the global transmission though it functions in local dimensions. Local conveyance is rare. The idea still taking shape behind the contemporary public communications is glocalization, i.e. mutual co-operation, binding both spaces together, especially global transmission and local reception. This is the so-called “third culture”. In this third culture, the book will no doubt retain its role within the educational and intellectual (reflexive) function, but it should rather change the character, space and the way of its informative effect, while there are many indications that its entertaining and compensative role will be admittedly reduced in various degrees.
The book in a local and regional environment